POLA KEPEMIMPINAN KYAI DI PESANTREN NURIS, NEGARA, BANYUBIRU DAN POTENSINYA SEBAGAI SUMBER BELAJAR SOSIOLOGI DI MA - Yanti, Dewi Kusuma; Mudana, I Wayan; Nur, Irwan (Jurnal Pendidikan Sosiologi Undiksha, 2024)
This study aims to find out (1) the pattern of leadership of the Kyai of the Nuris State Islamic Boarding School, Banyubiru (2) the policies and strategies of the Kyai in leading the Nuris Islamic Boarding School, Banyubiru (3) Aspects of leadership potential as a source of learning Sociology in MA/SMA. This study uses a descriptive qualitative approach. The methods used in collecting this data are observation, interviews, documentation and checking the validity of the data in the form of data collection triangulation and data source triangulation. As well as the methods and techniques of data analysis used in several stages such as data collection, data reduction, data presentation and verification/drawing conclusions. The results of the study show that the Kyai leadership pattern at the Nuris Negeri Banyubiru Islamic Boarding School has several leadership patterns such as the Kyai leadership pattern in the teachings of the prophet, the Kyai leadership pattern in accepting new students and the Kyai leadership pattern in the field of education. And carrying out policies, there are several policies that are used by Islamic boarding schools for rewards and punishments and strategies used by educational strategies and social strategies and aspects of leadership patterns that can be used as learning resources in sociology subjects in SMA/MA